Knowledge about spychologocal violence and its relation with psycho- social factors in young adult women - Lorena Fabiola Velásquez Chalán; Rubén García Núñez; Juan Manuel Armendáríz Tubón; María Aurelia San Juan Bosch; Alexis Díaz Brito (Medisur, 2019)
Foundation: psychological violence is a multifactorial phenomenon associated to bio-social factors which promote it. It still is a health problem. Objective: to determine knowledge about psychological violence and their relation with bio-social factors in Young adult women. Methods: cross descriptive study realized at the Lacas San Vicente neighborhood, Ecuador from January to June 2016. The universe of 146 young adult women (20 – 39 years old) was applied a questionnaire, validated by a group of experts, structured in two parts: an initial one which collected data about socio-demographic variables and another one with a knowledge test. For the relationship among variables it was used the squared-chi test with a level of significance lower than 5 % (p=< 0,05). Results: 28% were between 20 and 24 years old similarly to the 30-34 age group; 49% are housewives and of elementary schooling; 68% had a stable partnership; 71% lives with their partners who consume alcoholic beverages; 60% had antecedents of violence at home. The 99% are catholic; 43% formed a nuclear family. The non-satisfactory knowledge about psychological violence predominated (98%); 76% did not know about laws and ways of preventing violence; 99% did not know about the consequences of psychological violence. A statistically significant relation was found between the non-satisfactory knowledge and the level of instruction (p=0, 02) and occupation (p=0,004). Conclusion: knowledge about psychological violence is not satisfactory; the low instruction and the lack of labor relationship promote ignorance.